PERAN INOVASI PRODUK DALAM MEMEDIASI PENGARUH ORIENTASI PASAR TERHADAP KINERJA PEMASARAN USAHA KECIL MENENGAH - Adiya Putri, Ni Kadek Mutiara; Aksari, Ni Made Asti; Warmika, I Gde Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.12.TAHUN.2023DO - 10.24843/EEB.2023.v12.i12.p11, 2023)
Amid a pandemic, companies are required to be able to make new innovations by paying close attention to customer needs to improve marketing performance. The purpose of this study is to determine the role of product innovation in mediating the effect of market orientation on marketing performance of small and medium enterprises (SMEs). This research uses non-probability sampling method using saturated sampling technique with 64 respondents. Data was collected using questionnaire and analysed using path analysis. The results of this study show that market orientation has nonsignificant positive effect on marketing performance, market orientation has significant positive effect on product innovation, product innovation has nonsignificant positive effect on marketing performance and product innovation is unable to mediate the effect of market orientation on marketing performance of SMEs of gold and silver jewelery in Singapadu village. This study can be used as a refrence for future studies on topics concerning marketing performance.